Oxidative stress in HIV positive children - Dias, Bina F.; Srinivas, Aruna (International Journal of Research in Medical Sciences, 2017)
Background: The objective is to assess oxidative stress by measuring the concentration of malondialdehyde in HIV positive children and compare it with normal children (not suffering from any disease) of the same age group. Methods: In this prospective comparative study, we analysed malondialdehyde in 80 HIV positive children in the age group of 6-12 yrs from lower socio-economic strata and compared the values with 85 normal children not infected by any disease, of the same age group and similar socio-economic strata at L.T.M.M. College. Estimation of Malondialdehyde was carried out by using the method of SADASIVUDU by thiobarbituric acid reaction. Results: The level of Malondialdehyde was significantly higher in HIV positive children than in controls. Conclusions: The increased levels of Malondialdehyde confirm the involvement of oxidative stress in the pathophysiology of this infection in children